BBC World Service - Johnston, Gordon. author. aut Link
X, 338 p. 1 illus.
Keywords: This book is the first full-length history of the BBC World Service: from its interwar launch as short-wave radio broadcasts for the British Empire, to its twenty-first-century incarnation as the multi-media global platform of the British Broadcasting Corporation. The book provides insights into the BBC’s working relationship with the Foreign Office, the early years of the Empire Service, and the role of the BBC during the Second World War. In following the voice of the BBC through the Cold War and the contraction of the British empire, the book argues that debates about the work and purposes of the World Service have always involved deliberations about the future of the UK and its place in the world. In current times, these debates have been shaped by the British government’s commitment to leave the European Union and the centrifugal currents in British politics which in the longer term threaten the integrity of the United Kingdom. Through a detailed exploration of its past, the bookposes questions about the World Service’s possible future and argues that, for the BBC, the question is not only what it means to be a global broadcaster as we enter the third decade of the twenty-first century, but what it means to be a national broadcaster in a divided kingdom.